PENINGKATAN KECAKAPAN MATEMATIS SISWA MELALUI PENDEKATAN SAINTIFIK BERBASIS DISPOSISI MATEMATIS DI SMP - Christianti, Tarsila; Sugiatno, Sugiatno; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to find out the improvement of students' mathematical skills through a disposition-based scientific learning approach in the St. Benedict Pahauman Middle School. The research method used in this research was pedagogical action research. The stages carried out in this study were observing, reflecting, planning, acting. The subjects of this study were 10 students of class IX C of SMP St. Benedict Pahauman in the academic year 2018/2019. Data collection techniques used in this study were test and non-test techniques in the form of observation sheets / observation sheets of teacher activities and disposition questionnaires. The data that has been obtained in this study were analyzed by qualitative descriptive methods. Based on the results of research and discussion, in this study it could be concluded that there was an increase in students' mathematical skills after learning a scientific approach based on disposition and was classified as high. Â Keywords: Mathematical Skills, Scientific Learning Approaches, Pedagogical Action Research, and Disposition